Autoantibodies in sarcoidosis: Innocent bystander or promising biomarker for organ involvement? - Pozzan, Riccardo; Salton, Francesco; Confalonieri, Paola; Trotta, Liliana; Barbieri, Mariangela; Reccardini, Nicolò; Torregiani, Chiara; Screm, Gianluca; Hughes, Michael; Baratella, Elisa; Confalonieri, Marco; Mondini, Lucrezia; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Sarcoidosis is a rare inflammatory disease that can affect any organ in the body, but most commonly involves lungs and lymph nodes. Sarcoidosis is often considered an autoimmune disease, attributed to many factors, including autoantigen-specific T cells, antibodies producing B lymphocytes, autoimmune inflammation, although its exact cause and classification are still under debate.The aim of our study was to evaluate the possible role of autoantibodies, such as anti-nuclear (ANA), extractable nuclear antigen (ENA) and antiphospholipids, in sarcoidosis patients. Methods: We conduct a retrospective study on our patients with confirmed diagnosis of sarcoidosis involving lungs, lymph nodes and multiple organs, and we collected and analyzed data on blood and urine tests (C-reactive protein, CRP, amount of calcium in blood and urine, CD4/CD8 ratio, lymphocyte count), lung function, radiological patterns, ongoing treatments (steroid therapy, hydroxychloroquine or methotrexate, other immunosuppressive agents). Results: We enrolled 328 sarcoidosis patients, and we focused our attention on 32 patients with positive ANA antibodies (11%), observing a high percentage of them with sarcoidosis involving the lungs (77%), but more specifically a significant discrepancy, in percentage terms, in the blood CD4/CD8 ratio. In the ANA-positive group we observed 26% of patients with a high blood CD4/CD8 ratio (average CD4/CD8 ratio of 2.41), whereas in the ANA-negative group, patients with a high CD4/CD8 ratio (average ratio 1.78) represented a much smaller percentage (13%). This finding may be a source of further investigation for other studies on the topic. Conclusions: Analysis of autoantibodies expressed in our case series did not identify a specific autoantibodies pattern in sarcoidosis. Few studies have analyzed autoantibody patterns in sarcoidosis patients and involved smaller populations. In conclusion, our study evaluates a sizable population, and underlines the need for further, larger clinical studies to evaluate possible associations between sarcoidosis and autoimmunity.